Seroprevalence of toxoplasma gondii infection in refugee and migrant pregnant women along the Thailand–Myanmar border - van Enter, B; Lau, Y; Ling, C; Watthanaworawit, W; Sukthana, Y; Lee, W; Nosten, F; McGready, R (American Society of Tropical Medicine and Hygiene, 2017)
Toxoplasma gondii primary infection in pregnancy is associated with poor obstetric outcomes. This study aimed to determine the seroprevalence of Toxoplasma infection in pregnant migrant and refugee women from Myanmar attending antenatal care in Thailand. A random selection of 199 residual blood samples from first antenatal screen in 2014–2015 was tested for Toxoplasma IgG and IgM antibodies. Seroprevalence of Toxoplasma infection was 31.7% (95% confidence interval = 25.6–38.4). Avidity testing in the three positive IgM cases indicated all were past infections. Multiparity (≥ 3 children) was significantly associated with higher Toxoplasma seropositivity rates. Seroprevalence of T. gondii infection in this pregnant population is similar to the only other report from Myanmar, and was significantly associated with multiparity. Toxoplasma infection is important in pregnant women. Nevertheless, in this marginalized population, this infection may be given less priority, due to resource constraints in providing the most basic components of safe motherhood programs.